2022
DOI: 10.1186/s12933-022-01602-9
|View full text |Cite
|
Sign up to set email alerts
|

MLKL-mediated necroptosis is a target for cardiac protection in mouse models of type-1 diabetes

Abstract: Background Cardiomyocyte death contributes to cardiac pathology of diabetes. Studies have shown that the RIPK3/MLKL necroptosis signaling is activated in diabetic hearts. Deletion of RIPK3 was reported to attenuate myocardial injury and heart dysfunction in streptozocin (STZ)-induced diabetic mice, suggesting a potential role of necroptosis in diabetic cardiomyopathy. This study characterized cardiomyocyte necroptosis in diabetic hearts and investigated whether MLKL-mediated necroptosis is a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Noteworthy, necroptosis of distinct cells in different organs (including hepatic stellate cells, pancreatic stellate cells, fibroblasts and myofibroblasts) may cause fibrosis 42 . In diabetic cardiomyopathy, aggravated oxidative stress and promoted necroptosis exacerbated myocardial fibrosis 40,43 . Apoptotic adipocytes promoted necroptosis of macrophage foam cells to activate collagen synthesis in fibroblasts via a paracrine manner 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, necroptosis of distinct cells in different organs (including hepatic stellate cells, pancreatic stellate cells, fibroblasts and myofibroblasts) may cause fibrosis 42 . In diabetic cardiomyopathy, aggravated oxidative stress and promoted necroptosis exacerbated myocardial fibrosis 40,43 . Apoptotic adipocytes promoted necroptosis of macrophage foam cells to activate collagen synthesis in fibroblasts via a paracrine manner 44 .…”
Section: Discussionmentioning
confidence: 99%
“…42 In diabetic cardiomyopathy, aggravated oxidative stress and promoted necroptosis exacerbated myocardial fibrosis. 40,43 Apoptotic adipocytes promoted necroptosis of macrophage foam cells to activate collagen synthesis in fibroblasts via a paracrine manner. 44 Tubulointerstitial fibrosis was mediated by necroptosis of renal tubular epithelial cells in patients with chronic kidney disease via TGF-β 1 /Smad3 signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis combines both necrosis and apoptosis, hence the term necroptosis ( Vanden Berghe et al, 2014 ). It is a regulated form of necrotic cell death mediated by receptor-interacting kinase 1 (RIPK1), receptor-interacting protein kinase 3 (RIPK3), and mixed lineage kinase domain-like (MLKL) ( Conrad et al, 2016 ; Cao et al, 2022 ). RIPK1 activates RIPK3 and thereby recruits MLKL at the cell membrane, which causes membrane rupture and eventually triggers necroptosis ( Samson et al, 2021 ; Gupta et al, 2022 ).…”
Section: The Crosstalk Between Ferroptosis and Other Traditional Cell...mentioning
confidence: 99%
“…SIRT3‐knockout diabetic mice exhibited more severe cardiac dysfunction, exacerbated mitochondrial dysfunction, excessive ROS production, promoting necroptosis, and worsening DCM compared with the control group, indicating that SIRT3 could serve as a therapeutic target for DCM. Cao et al (2022) found that pharmacological inhibition or knockout of RIPK3 or MLKL in STZ‐induced type‐1 diabetic mice could attenuate necroptosis and protect cardiac cells subjected to high glucose treatment. Furthermore, the study demonstrated that Empagliflozin and metformin could prevent the phosphorylation of RIPK3 and MLKL in cardiac cells under high glucose conditions and inhibit necroptosis, providing benefits for cardiovascular complications in diabetic patients.…”
Section: Pcd and Dcmmentioning
confidence: 99%
“…Long noncoding RNA DCRF is upregulated in DCM, activating autophagy, accelerating myocardial fibrosis, and promoting the progression of DCM (Feng et al, 2019). Necroptosis plays an essential role in the pathological process of DCM, and research evidence suggests that MLKL‐mediated necroptosis contributes to DCM (Cao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%